Airfoil Surface Forming and Conformity Test Using Laser Tracker - Habtamu Beri; Perumalla Janaki Ramulu (Advances in Materials Science and Engineering)
In this study, NACA0018 airfoil surface conformity test was conducted using API tracker3 in combination with SpatialAnalyzer (SA) and modeling software SolidWorks. Plaster of Paris is used as a plug making material and a woven-type fiberglass is used as mold and airfoil surface making material. For airfoil surface analysis, three-dimensional model of the airfoil surface was developed in SolidWorks software and imported in IGES file format to SpatialAnalyzer (SA) software. Then, measurements were taken from manufactured airfoil surface using laser tracker through surface scanning method. Surface conformity test was conducted through fitting of measured points to surface model imported from SolidWorks to SpatialAnalyzer (SA) software. The optimized fit summary result shows that the average fit difference is 0.0 having standard deviation from 0.22224 from the average and zero with RMS of 0.2210. The maximum magnitude of the difference including x and y together is 0.5336 and the minimum −0.5077. Thus, with a given range of surface quality specification, laser tracker is an easy and reliable measurement and inspection tool to be considered.